Seven Decades of Gender Differences in German Voting Behavior - Ansgar Hudde (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
This article describes long-term changes in gender differences in voting behavior in Germany, using a~globally unique data source: information from real ballots. Compared with self-reports in available surveys, actual votes counted by gender and age groups have three advantages: neither representativeness issues nor social desirability bias, a~huge sample, and coverage of seven decades, beginning in 1953. Besides party-specific voting patterns, I~analyze summary measures for gender dissimilarities, both overall and separated by age groups. The modern gender gap—women voting more left-wing than men—first appeared in Germany in the 2017 election, surprisingly late compared with previous international research. The speed and structure with which the modern gender gap grew suggest that it is due to period effects rather than cohort effects. The modern gender gap differs by age group and, in post-World War~II Germany, women and men have never been as divided about politics as the youngest voters in 2021. These findings partly contrast with previous survey-based results. To explore whether this contrast stems from the smaller sample sizes of previous studies or gendered survey bias (e.g., more social desirability bias among women), I~compare results from real ballots with estimates from two survey data sources. Findings suggest that large surveys might provide reasonable estimates at the aggregate level but might overestimate the gender gap for more radical parties such as the AfD (Alternative for Germany).
Keywords: 300; Political sociology; Modern gender gap; Germany; Survey bias; Social desirability bias; Politische Soziologie; Umfrageforschung; Soziale Erwünschtheit; Repräsentative Wahlstatistik